(untitled) (The Pakistan Development Review, 1985)
The problem of the sex ratio fascinates social scientists. Some measure it through the masculinity ratio (number of men per woman), others use the feminity ratio (number of women per man). Among the latter is the majority of social scientist on this subcontinent e.g., Gupta [13 ; maps 24,25,26 and 27) and in several countries of continental Europe [66, fn. 33, p. 3] . Corrado Gini, the celebrated creator of various indices, popular in social Sciences, devoted to the topic his very first book [11]. Sex and gender is one of the most important and popular variables, on which a social scientist breaks up his data into Significantly different groups.